Immunoglobulin G4 Sclerosing Cholangitis: An Unusual Cause of Obstructive Jaundice—Case Report and Literature Review - Pragya Shrestha; Brian Le; Brent Wagner; William Pompella; Paras Karmacharya (Case Reports in Rheumatology)
IgG4-related sclerosing cholangitis (IgG4-SC) is one of the most common extra-pancreatic manifestation of IgG4-related disease (IgG4-RD) and is clinically distinct from primary sclerosing cholangitis (PSC). IgG4-RD is an increasingly recognized immune-mediated fibroinflammatory systemic disease, mostly affecting middle-aged and older male populations that can affect multiple organs. The presence of extra-biliary clinical manifestations of IgG4-RD, such as parotid and lacrimal swelling, lymphadenopathy, autoimmune pancreatitis, and retroperitoneal fibrosis, if present could provide important clues to diagnosis. High serum IgG4 levels, characteristic radiological (e.g., sausage-shaped pancreas or periaortitis) or biopsy findings (high percentage of IgG4+ plasma cells, lymphoplasmacytic infiltrate, storiform fibrosis, or obliterative phlebitis) in the setting of these features is diagnostic of this disease process. However, isolated IgG4-SC might be a diagnostic challenge, and the distinction is important as management of this disorder is vastly different from other causes of cholangitis such as PSC. Systemic corticosteroid therapy is the mainstay of therapy.